Overexpression of the multidrug resistance gene mdr3 in spontaneous and chemically induced mouse hepatocellular carcinomas. - Teeter, L D (1990)
Overexpression of a family of plasma membrane glycoproteins, known as P-glycoproteins, is commonly associated with multidrug resistance in animal cells. In rodents, three multidrug resistance (mdr or pgp) genes have been identified, but only two can confer the multidrug resistance phenotype upon transfection into animal cells. Using the RNase protection method, we demonstrated that the levels of three mdr gene transcripts differ among mouse tissues, confirming a previous report that the expression of these genes is tissue specific (J.M. Croop, M. Raymond, D. Huber, A. DeVault, R. J. Arceci, P. Gros, and D. E. Housman, Mol. Cell. Biol. 9:1346-1350, 1989). The levels of mdr transcripts were determined for mouse liver tumors spontaneously arising in both C3H/HeN and transgenic animals containing the hepatitis B virus envelope gene and for tumors induced by two different carcinogenic regimens in C57BL/6N and B6C3-F1 mice. The mdr3 gene was overexpressed in all 22 tumors tested. Our results demonstrate that overexpression of the mdr3 gene in mouse liver tumors does not require exposure of the animals to carcinogenic agents and suggest that its overexpression is associated with a general pathway of hepatic tumor development. The overexpression of the mdr3 gene, which is the homolog of human mdr1 gene, in hepatocellular carcinomas may be responsible for the poor response of these tumors to cancer chemotherapeutic agents.